TAXONOMY AND RELATIONSHIP OF CYBERCRIMES AND SECURITY MEASURES BEFORE AND DURING COVID-19: A SEM APPROACH - Mohan, Dr. (Ms.) Tarannum (The journal of contemporary issues in business and government, 2022)
The aim of this study was to understand how most vulnerable section that is girl students classifies cybercrimes and security measures before and after advent of pandemic. In qualitative aspect, types of cybercrime and corresponding security measures were judged through personal interview of experts. The quantitative aspect used deduced dimensions to collect data from randomly selected 510 girl students from under-graduate colleges of nine major cities of Punjab. SEM analysis was applied to examine responses to latent dimensions. Four attributes of cybercrimes were classified, namely, stalking, privacy violation, financial risks and pornography. To counter these crimes three cyber security measures of general security, password protection and awareness about attacks were categorized. Lastly, significant difference was found between understanding of various cybercrimes and application of various security measures before and during pandemic.